Minimal overlap in language control across production and comprehension: Evidence from read-aloud versus eye-tracking tasks. (May 2020) - Ahn, Danbi; Abbott, Matthew J.; Rayner, Keith; Ferreira, Victor S.; Gollan, Tamar H.
Abstract: Bilinguals are remarkable at language control —switching between languages only when they want. However, language control in production can involve switch costs . That is, switching to another language takes longer than staying in the same language. Moreover, bilinguals sometimes produce language intrusion errors, mistakenly producing words in an unintended language (e.g., Spanish–English bilinguals saying "pero" instead of "but"). Switch costs are also found in comprehension. For example, reading times are longer when bilinguals read sentences with language switches compared to sentences with no language switches. Given that both production and comprehension involve switch costs, some language–control mechanisms might be shared across modalities. To test this, we compared language switch costs found in eye–movement measures during silent sentence reading (comprehension) and intrusion errors produced when reading aloud switched words in mixed–language paragraphs (production). Bilinguals who made more intrusion errors during the read–aloud task did not show different switch cost patterns in most measures in the silent–reading task, except on skipping rates. We suggest that language switching is mostly controlled by separate, modality–specific processes in production and comprehension, although some points of overlap might indicate the role of domain general control and how it can influence individual differences in bilingual language control. Highlights: Switch costs on production and comprehension were measured in separate tasks. Reading aloud mixed–language paragraphs induced language intrusion errors. Silent reading times slowed down on target words with language switches. Switch costs in two tasks were not associated in any measures but skipping rates. Language–control processes are mostly separate across production and comprehension.